Harvard business review on effective communication (Harvard Business School P. BostonUS, 1999)
Emphasizes the importance of listening, and provides suggestions for developing a listening improvement programme for the workplace. Provides guidelines for conducting meetings that achieve their objectives. Identifies communication, support, respect, fairness, predictability and competence as the factors which affect the development of trust and candour between staff and managers. Discusses the necessity for developing an information network that attracts, creates and disseminates information. Examines topics such as: changing the behaviour of frontline employees; and, building effective management teams.
Located in the Learning Resource Centre